2000
DOI: 10.1524/ract.2000.88.3-4.239
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS analyses of technetium(I) carbonyl complexes – stability studies in solutions

Abstract: EXAFS analyses were successfully used to determine the structure of Re and Tc carbonyl thioether complexes in solid and liquid samples. In connection with chromatographic and mass spectrometric methods the behaviour of Tc carbonyl dithioether complexes in aqueous solution was studied. It was found that complexes containing a bidentate thioether ligand are able to react with water by exchange of the chloride ion, which results in the formation of a cationic complex. As expected, the exchange proceeds faster at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
(13 reference statements)
2
6
0
Order By: Relevance
“…The Hartree-Fock calculation followed by a Møller-Plesset correlation energy correction, truncated at secondorder (MP2) yielded the second lowest total energy, spent only 17% longer CPU time than the HFB method. It also produced Tc-C and Tc-O bond lengths closest to those determined with EXAFS by Seifer et al 10,11 Therefore, we adopted the MP2/ CEP-121G method exclusively.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The Hartree-Fock calculation followed by a Møller-Plesset correlation energy correction, truncated at secondorder (MP2) yielded the second lowest total energy, spent only 17% longer CPU time than the HFB method. It also produced Tc-C and Tc-O bond lengths closest to those determined with EXAFS by Seifer et al 10,11 Therefore, we adopted the MP2/ CEP-121G method exclusively.…”
Section: Resultsmentioning
confidence: 94%
“…Only few compounds formed by lower oxidation-state Tc were investigated for the same purpose owing to the lack of suitable Tc precursors. Although technetium carbonyls, such as Tc 2 (CO) 10 , have long been known, unfortunately, they have to be synthesized at a high temperature and under a high pressure. The situation was entirely changed by Alberto and his co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…The first task will provide an enhanced set of fundamental binding data relevant to speciation of non-pertechnetate alkaline soluble Tc in Hanford tank waste. It is known that the Tc(I) tricarbonyl moiety can complex with various mono-and polydentate organic molecules (Alberto et al 1998;Seifert et al 2000). The Hanford tanks contain a variety of organic complexants and degradation products.…”
Section: Approach: Examine Chemistry and Stability Of Tc(i) Carbonyl Complexesmentioning
confidence: 99%
“…Furthermore, recent research has shown that such substitutions for the water molecules in the Tc(I) tricarbonyl moiety can be a facile process (Lukens et al 2006a;Seifert et al 2000;Lukens et al 2004;Alberto et al 1998;Helm 2008). It is worth noting here that the possibility of replacing a carbonyl with a linear nitrosyl ligand to generate the neutral complex [(NO)(CO) 2 Tc(H 2 O) 3 ] or a similar derivative such as noted above is also a plausible candidate based on the available technetium XANES and EXAFS data.…”
Section: Sy 103mentioning
confidence: 99%